Population Pharmacokinetic Analysis to Support and Facilitate Switching from Risperidone Formulations to Rykindo in Patients with Schizophrenia - Wenyan Wang; Xiaofeng Wang; Ying Dong; David P. Walling; Pinglan Liu; Wanhui Liu; Yanan Shi; Kaoxiang Sun (Neurology and Therapy, 2024)
Abstract Introduction RYKINDO® (Rykindo) is a novel, long-acting injectable risperidone formulation administered biweekly (Q2W) through intramuscular gluteal injection for the treatment of schizophrenia in adult patients. This analysis was conducted to demonstrate that the clinical outcomes of Rykindo are equivalent to those of RISPERDAL CONSTA® (Consta; Q2W), and to establish a dosing methodology to switch from Consta to Rykindo, as well as to introduce Rykindo to patients who are currently on oral RISPERDAL® (Risperdal). Methods Population pharmacokinetic (PK) models for Rykindo and Consta were developed using a nonlinear mixed-effects model with the data from phase 1 studies. A model-based simulation was also conducted using NONMEM. Results The PK profiles of Rykindo and Consta were adequately represented by a one-compartment model with an immediate release followed by an intermediate and third main release. Drug release of Rykindo was faster than for Consta, reaching steady state approximately 2–3 weeks earlier. The exposures of the active moiety of Rykindo and Consta were comparable at steady state. Model-based simulation indicated that switching from Consta to Rykindo requires administration of the first Rykindo injection within 4–5 weeks following the last Consta injection. For patients taking Risperdal, introducing Rykindo with 1 week of Risperdal supplemental for once-daily dosing (QD) can achieve comparable or superior exposure to that of Consta with 3 weeks of oral QD supplements. A dosing window of ± 3 days for Rykindo was recommended. Conclusions This established approach provides guidance to physicians to initiate Rykindo therapy in adult patients with schizophrenia. Trial Registration ClinicalTrials.gov identifier, NCT02055287, NCT02186769 and NCT02091388.